2013
DOI: 10.1152/ajpendo.00389.2012
|View full text |Cite
|
Sign up to set email alerts
|

Muscle protein synthesis, mTORC1/MAPK/Hippo signaling, and capillary density are altered by blocking of myostatin and activins

Abstract: Loss of muscle mass and function occurs in various diseases. Myostatin blocking can attenuate muscle loss, but downstream signaling is not well known. Therefore, to elucidate associated signaling pathways, we used the soluble activin receptor IIb (sActRIIB-Fc) to block myostatin and activins in mice. Within 2 wk, the treatment rapidly increased muscle size as expected but decreased capillary density per area. sActRIIB-Fc increased muscle protein synthesis 1–2 days after the treatment correlating with enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
136
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(152 citation statements)
references
References 69 publications
15
136
1
Order By: Relevance
“…However, it was interesting to note that the differences between ActRIIB-Fc and ActRIIB-Fc-R groups were miniscule showing that physical activity did not have a noticeable further effect on trabecular bone in the murine femur in this model. ActRIIB-Fc-R mice ran significantly less especially in the beginning of the study as previously reported [26], which could at least in part explain the lack of additional effect of running on bone mass or strength in the ActRIIB-Fc-R group. The nonsignificant change between PBS and PBS running group in bone mineral density was also surprising suggesting that physical activity in a form of voluntary running does not greatly affect bone quality in long bones in young mdx mice.…”
Section: Discussionsupporting
confidence: 59%
“…However, it was interesting to note that the differences between ActRIIB-Fc and ActRIIB-Fc-R groups were miniscule showing that physical activity did not have a noticeable further effect on trabecular bone in the murine femur in this model. ActRIIB-Fc-R mice ran significantly less especially in the beginning of the study as previously reported [26], which could at least in part explain the lack of additional effect of running on bone mass or strength in the ActRIIB-Fc-R group. The nonsignificant change between PBS and PBS running group in bone mineral density was also surprising suggesting that physical activity in a form of voluntary running does not greatly affect bone quality in long bones in young mdx mice.…”
Section: Discussionsupporting
confidence: 59%
“…unpublished data) when protein synthesis is acutely already increased [19]. This suggests that the level of disruption to ER homeostasis through increased amounts of newly synthesized proteins by blocking AcvR2B ligands may not be severe enough to trigger a UPR ER response.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle homogenates mixed in Laemmli sample buffer were heated at 95°C to denature proteins and processed as described previously [19,25] …”
Section: Pdi Ire-1α Perk P-eif2α/eif2α Sirtuins Ampk Lysine Acementioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that the potent cell surface receptor ActRIIB binds and inhibits myostatin, leading to dramatic muscle growth (24)(25)(26). Based on this background, we hypothesized that the combination of these two agents would have a therapeutic advantage.…”
Section: Discussionmentioning
confidence: 96%